MEMBANGUN MADRASAH BERMUTU MELALUI PRAKTIK MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS POTENSI UMAT (Sebuah Alternatif Model Pembiayaan Pendidikan di Indonesia) - Umi Zulfa (Jurnal Kependidikan)
Zakat, infak, sadakah and wakaf are really potential financial sources of madrasah (school). If a madrasah is able to manage them creatively, tranparantly, and accountably for funding the running process of education, a high quality madrasah will be able to realized and it can be accesed by Muslim society in Indonesia. In addition, it shows that a management of society-based education finance can be the alternative model of education finance in Indonesia and offers a solution to the problem of education finance in Indonesia.